A Habitat-Template Approach to Green Wall Design in Mediterranean Cities - Miriam Patti; Carmelo Maria Musarella; Giovanni Spampinato (Buildings)
Integrating nature-based solutions into sustainable urban design has become increasingly important in response to rapid urbanization and climate-related environmental challenges. As part of these solutions, green walls not only enhance the thermal and acoustic performance of buildings but also contribute to urban ecosystem health by supporting biodiversity. In this context, the careful selection of plant species is essential to ensure ecological efficiency, resilience, and low maintenance. This study presents a model for selecting plant species suitable for natural green walls in Mediterranean cities, with a focus on habitats protected under Directive 92/43/EEC. The selection followed a multi-phase process applied to the native flora of Italy, using criteria such as chorological type, life form, ecological indicator values, altitudinal range, and habitat type. Alien and invasive species were excluded, favoring only native Mediterranean species adapted to local pedoclimatic conditions and capable of providing ecosystem, esthetic, and functional benefits. The outcome of this rigorous screening led to the identification of a pool of species suitable for green wall systems in Mediterranean urban settings. These selections offer a practical contribution to mitigating the urban heat island effect, improving air quality, and enhancing biodiversity, thus providing a valuable tool for designing more sustainable and climate-adaptive buildings.